The Effect of Job Satisfaction and Work-life Balance on Employee Turnover Intention in Real Estate Industry - Nadira Fasya Herliana; Agung Wahyu Handaru; Widya Parimita (LPPM Universitas Negeri Jakarta, 2021)
This study aims to: 1) To find out the description of job satisfaction, work-life balance, and turnover intention of generation Y employees in the real estate industry in Kebon Sirih, Central Jakarta, 2) To find out the effect of job satisfaction on turnover intention of generation Y employees in the real estate industry in Kebon Sirih, Central Jakarta, 3) To find out the effect of work-life balance on turnover intention of generation Y employees in the real estate industry in Kebon Sirih, Central Jakarta, 4) To find out how much the contribution of job satisfaction and work-life balance to turnover intention of generation Y employees in the real estate industry in Kebon Sirih, Central Jakarta. This research was conducted on 104 generation Y employees in the real estate industry in Kebon Sirih, Central Jakarta. Data collection technique using survey methods by distributing questionnaire which then processed with SPSS software version 25. This research used descriptive and explanatory analysis. The result of this study shows that the level of job satisfaction and work-life balance of generation Y employee in the real estate industry in Kebon Sirih, Central Jakarta are low, the level of turnover intention of generation Y employees in the real estate industry in Kebon Sirih, Central Jakarta is high, job satisfaction has a negative and significant effect on turnover intention, work-life balance has a negative and significant effect on turnover intention, and the model of job satisfaction and work-life balance can predict turnover intention of generation Y employee in the real estate industry in Kebon Sirih, Central Jakarta.